Bee Pollen Effect on Blood Glucose Levels in Alloxan-induced Male Wistar Rats - Rahayu, Aprilia Nurcahyaning; Wirjatmadi, Bambang; Adriani, Merryana; M., Soenarnatalina; Winarni, Dwi; Hartiningsih, Sri (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
a